Cholera Vibrio Membrane Protein OmpT as an Omptin Belonging to Vibrionaceae Family - B. N. Mishan’Kin; O. V. Duvanova; L. V. Romanova; E. S. Shipko; A. S. Vodop’Yanov (Проблемы особо опасных инфекций, 2014)
Concerned are the issues related to enterobacteria omptins, their structure and functionality, as well as alternative role in pathogenesis of the infections induced by them. Isolated from cholera vibrio, and later purified using differential centrifugation and column chromatography has been porin protein of the OmpT outer membranes, with the molar mass of approximately 40 kDa. Synthesis of porin is under control of the complex regulatory system. It does not contain cysteine, but possesses proteolytic activity with broad substrate specificity: it hydrolyzes fibrin, protamin, gelatine; transduces human plasminogen into plasmin, which provides for the well-known advantages for the vibrios in the intestine of a susceptible host. Comparative computer-assisted analysis of amino acid sequence has revealed that cholera vibrio OmpT protein relates to the omptins of enterobacteria as a far-remotely one, and has 13 % identity and similarity to it. OmpT protein is probably affiliated to a new class of porins of the family Vibrionaceae .